Evaluating the economic impact of a preventative seismic legislation in Ecuador - Ponce, Juan; Salazar, Andrés (Advances in Social Sciences Research Journal, 2020)
At the end of 2013 a compulsory inspection policy was introduced in Quito-Ecuador to ensure that new buildings complied with seismic resistant design requirements. This policy could affect the economic sector of construction by increasing the cost of buildings. It is in this context that this paper analyses the economic impact of the new construction policy. Given that this policy only applied to the canton of Quito and not to any other canton in Ecuador, the paper creates a synthetic control group on the basis of infrastructure and socio-economic data of the fifteen most heavily populated cantons in the country. The results show a statistically significant and negative impact. In other words, although the new policy succeeded in improving the seismic resistant quality of buildings in the canton of Quito, at the same time it had a negative effect on the per capita gross value added of the construction sector.